2021
DOI: 10.21203/rs.3.rs-757623/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondria-Targeted Nanoplatforms For Enhanced Photodynamic Therapy Against Hypoxia Tumor

Abstract: Background: Photodynamic therapy (PDT) is a promising therapeutic modality that can convert oxygen into cytotoxic reactive oxygen species (ROS) via photosensitizers to halt tumor growth. However, hypoxia and the unsatisfactory accumulation of photosensitizers in tumors severely diminish the therapeutic effect of PDT. In this study, a multistage nanoplatform is demonstrated to overcome these limitations by encapsulating photosensitizer IR780 and oxygen regulator 3-bromopyruvate (3BP) in poly (lactic-co-glycolic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Our findings demonstrating that DΨ m decreased following PDP are similar to those reported by others (78)(79)(80)(81)(82)(83)(84)(85). For example, Singh et al (84) reported that the fluorescence of Rhodamine-123, a dye that localizes to viable mitochondrial membranes, delocalized and filled the cell cytoplasm following PDT with Photofrin II as a photosensitizer, indicating that mitochondria are among the targets of Photofrin II-mediated PDT.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings demonstrating that DΨ m decreased following PDP are similar to those reported by others (78)(79)(80)(81)(82)(83)(84)(85). For example, Singh et al (84) reported that the fluorescence of Rhodamine-123, a dye that localizes to viable mitochondrial membranes, delocalized and filled the cell cytoplasm following PDT with Photofrin II as a photosensitizer, indicating that mitochondria are among the targets of Photofrin II-mediated PDT.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the efficacy of several treatment methods, such as chemotherapy, radiotherapy, and immunotherapy, would be influenced by cancer-related hypoxia. [3][4][5] The abnormal characteristics of the tumor microenvironment are prone to form transport barriers, which limits the speed and range of drug delivery at the tumor site, 6 leading to a reduction in the efficacy of drugs. The application of conventional chemotherapy exerts different adverse effects.…”
Section: Introductionmentioning
confidence: 99%